Normal-temperature high-light-transmittance phase change film and preparation method thereof

By using acrylate polymerization phase change monomers and diacrylate polymerization crosslinking agents for radical polymerization, a phase change film with high light transmittance is prepared, which solves the problem of insufficient light transmittance and transparency of existing phase change materials at room temperature, and realizes thermal management application in transparent scenarios in room temperature.

CN119591777APending Publication Date: 2025-03-11BEIFANG UNIV OF NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580159.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing phase change materials based on solid-liquid phase change are prone to morphological instability and leakage after being higher than their phase change temperature, and the light transmittance and transparency at room temperature are insufficient, which limits their application scenarios.

Method used

Octadecyl acrylate or hexadecyl acrylate is used as polymerized phase change monomers, combined with 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, etc. as polymerization crosslinking agents, and a crosslinking product is obtained through radical polymerization to prepare a phase change film with high light transmittance at room temperature.

Benefits of technology

The prepared phase change film has a transparent appearance at room temperature and has a light transmittance of more than 95%, which solves the problems of low light transmittance and low transparency at room temperature, broadens the application scenarios of phase change materials, and shows excellent results in the field of thermal management of photovoltaic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122846080000081
    Figure BDA0005122846080000081
  • Figure HDA0005122846090000011
    Figure HDA0005122846090000011
  • Figure HDA0005122846090000012
    Figure HDA0005122846090000012
Patent Text Reader

Abstract

The invention provides a normal-temperature high-light-transmittance phase change film and a preparation method thereof, and the preparation method comprises the following steps: dissolving a polymeric phase change monomer, a polymeric cross-linking agent and an initiator in a solvent to obtain a solution; wherein the polymeric phase change monomer is one or a combination of two of octadecyl acrylate and hexadecyl acrylate; the polymerization cross-linking agent is one or a combination of more of 1, 6-hexanediol diacrylate, 1, 4-butanediol diacrylate and ethylene glycol diacrylate; and injecting the prepared solution into a mold, carrying out heat treatment, and drying at normal temperature to obtain the transparent phase change film. The phase change film prepared by the preparation method disclosed by the invention has good transparency and light transmittance in a visible light region at normal temperature, the light transmittance can reach 95% or above, the problems of low light transmittance and low transparency of a current phase change material at normal temperature are solved, and the application in the field of thermal management in a normal-temperature transparent scene is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change materials, and in particular relates to a normal-temperature high-transmittance phase change film and a preparation method thereof. Background Art

[0002] Phase change materials can absorb and release a large amount of latent heat under temperature changes and have a wide range of applications in the field of thermal management. Solid-liquid phase change and solid-solid phase change are the two most studied basic phase changes. However, phase change materials based on solid-liquid transition face the problems of morphological instability and leakage, that is, because components, such as paraffin, fatty acids, polyols and other substances, will melt from solid to liquid after exceeding their phase change temperature, which is not conducive to the practical application of phase change materials. Although many studies are devoted to modification through physical encapsulation (such as constructing core-shell structures and aerogel networks), there is still a risk of leakage. On the contrary, solid-solid phase change materials through chemical cross-linking rarely have the risk of leakage and deformation.

[0003] Solid-solid phase change materials maintain stability by fixing phase change segments at the molecular level through covalent bonds. The preparation of these materials involves the grafting, copolymerization, self-polymerization and cross-linking of organic solid-liquid phase change materials, which ensures the macroscopic stability of the materials during the phase change process. However, most of these phase change materials have a white or light yellow appearance at room temperature, and therefore have extremely weak transmittance in the visible light region, resulting in a lack of application of phase change materials in room temperature transparent scenarios. Therefore, it is necessary to develop phase change materials with high transmittance at room temperature to expand the application scenarios of phase change materials. Summary of the invention

[0004] In view of this, in order to solve the above technical problems, the present invention proposes a room temperature high transmittance phase change film and a preparation method thereof. The prepared transparent phase change film has a transparent appearance in the visible light region at room temperature and excellent transmittance.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A method for preparing a room-temperature high-transmittance phase change film comprises the following steps:

[0007] S1. Dissolving a polymerized phase change monomer, a polymerized cross-linking agent and an initiator in a solvent to obtain a solution; wherein the polymerized phase change monomer is one or a combination of octadecyl acrylate and hexadecyl acrylate; and the polymerized cross-linking agent is one or a combination of 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate and ethylene glycol diacrylate;

[0008] S2. Injecting the prepared solution into a mold, heat treating it, and drying it at room temperature to obtain the transparent phase change film.

[0009] In some preferred embodiments of the method for preparing a phase change film with high light transmittance at room temperature of the present invention, the initiator is a combination of one or more of azobisisobutyronitrile, azodimethylcapronitrile and dibenzoyl peroxide.

[0010] In some preferred embodiments of the method for preparing a phase change film with high light transmittance at room temperature of the present invention, the solvent is a combination of one or more of tetrahydrofuran, dichloromethane, ether and chloroform.

[0011] In some preferred embodiments of the method for preparing a phase change film with high light transmittance at room temperature of the present invention, the mass ratio of the polymerized phase change monomer to the polymerized cross-linking agent is 10:1-3.

[0012] In some preferred embodiments of the method for preparing a phase change film with high light transmittance at room temperature of the present invention, the volume ratio of the total mass of the polymerized phase change monomer and the polymerized cross-linking agent to the solvent is 0.2-0.5 g / ml.

[0013] In some preferred embodiments of the method for preparing the room-temperature high-light-transmittance phase-change film of the present invention, the molar amount of the initiator accounts for 0.1% to 10% of the total molar amount of the polymerized phase-change monomer and the polymerized cross-linking agent.

[0014] In some preferred embodiments of the method for preparing a phase change film with high light transmittance at room temperature of the present invention, the heat treatment is specifically: continuing the reaction at 60 to 150° C. for 2 to 24 hours.

[0015] The second aspect of the present invention provides a room-temperature high-transmittance phase change film prepared by the preparation method.

[0016] The third aspect of the present invention provides an application of the room temperature high light transmittance phase change film in the field of thermal management in a room temperature transparent scene.

[0017] Compared with the prior art, the room temperature high light transmittance phase change film and the preparation method thereof described in the present invention have the following advantages:

[0018] (1) The preparation method of the present invention uses octadecyl acrylate or hexadecyl acrylate as a base, uses three different diacrylic acid monomers as crosslinking agents, obtains a crosslinked product through free radical polymerization, and then prepares a phase change film. Due to the internal crystal characteristics, the phase change film presents a transparent appearance at room temperature and has good light transmittance in the visible light region at room temperature;

[0019] (2) The room-temperature high-transmittance phase change film of the present invention has good transparency and transmittance in the visible light region at room temperature, and the transmittance can reach more than 95%, which solves the problem of low transmittance and low transparency of current phase change materials at room temperature, broadens the application scenarios of phase change materials, and can realize the application in the field of thermal management under room-temperature transparent scenarios;

[0020] (3) The room temperature high transmittance phase change film described in the present invention can be used as a thermal management material for photovoltaic cells to effectively maintain the photoelectric conversion efficiency of solar cells. Under the same solar radiation, the photoelectric conversion efficiency of polycrystalline silicon solar cells encapsulated with the room temperature high transmittance phase change film described in the present invention is 2% higher than that of unencapsulated samples within a certain period of time, which provides a basis for the preparation of photovoltaic-thermoelectric coupling systems, further improves the utilization efficiency of solar energy, and also helps to solve the contradiction of thermal energy in space and realize the effective transfer of thermal energy in space after heat-to-electricity conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a transparency comparison diagram of the transparent phase change film prepared in Example 1 and a blank sample;

[0022] Figure 2 The infrared analysis diagram of the transparent phase change film prepared in Example 1 and the raw materials required for its preparation;

[0023] Figure 3 The temperature-photoelectric conversion efficiency curves of the transparent phase change film encapsulated solar cell panel prepared in Example 1 and the blank unencapsulated solar cell panel;

[0024] Figure 4 The actual pictures are of the transparent phase change film encapsulated solar cell panel prepared in Example 1 and a blank unencapsulated solar cell panel. DETAILED DESCRIPTION

[0025] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0026] The present invention will be described in detail below with reference to the embodiments and the accompanying drawings.

[0027] The steps for preparing a phase change film with high light transmittance at room temperature are as follows:

[0028] Step 1, dissolving a polymerizable phase change monomer, a polymerizable cross-linking agent and an initiator in a solvent to obtain a solution;

[0029] The polymerizable phase change monomer is one or a combination of octadecyl acrylate and hexadecyl acrylate; the polymerizable crosslinking agent is one or a combination of 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, and ethylene glycol diacrylate; the initiator is one or a combination of azobisisobutyronitrile, azodimethylcapronitrile, and dibenzoyl peroxide; the solvent is one or a combination of tetrahydrofuran, dichloromethane, ether, and chloroform;

[0030] The mass ratio of the polymerized phase change monomer to the polymerized cross-linking agent is 10:1-3; the volume ratio of the total mass of the polymerized phase change monomer and the polymerized cross-linking agent to the solvent is 0.2-0.5 g / ml; the molar amount of the initiator accounts for 0.1%-10% of the total molar amount of the polymerized phase change monomer and the polymerized cross-linking agent;

[0031] Step 2: inject the prepared solution into a mold, place the mold in a reaction container, and perform a temperature-controlled heat treatment at 60 to 150° C. for 2 to 24 hours, and then dry at room temperature to obtain the transparent phase change film.

[0032] Example 1

[0033] 2 g of octadecyl acrylate, 0.14 ml of 1,6-hexanediol diacrylate and 5 mg of azobisisobutyronitrile were dissolved in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0034] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0035] The prepared phase change film and its raw materials were subjected to infrared analysis, such as Figure 1 As shown, 1,6-hexanediol diacrylate is at 3407 cm -1 and 3342cm -1 The characteristic hydroxyl band at 1635cm -1 A peak appears at the position corresponding to the vinyl group, confirming the substitution of the hydroxyl group; in the spectrum of polyoctadecyl acrylate, the absence of the vinyl peak confirms the progress of the polymerization reaction; analysis of the phase change film prepared in Example 1 found that the vinyl peaks of 1,6-hexanediol diacrylate and octadecyl acrylate disappeared, indicating that free radical polymerization leads to cross-linking, thereby forming a long-chain macromolecular structure, and cross-linking is completed inside the material.

[0036] Example 2

[0037] 2 g of octadecyl acrylate, 0.14 ml of 1,4-butanediol diacrylate and 5 mg of azobisisobutyronitrile were dissolved in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0038] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0039] Example 3

[0040] Dissolve 2 g of octadecyl acrylate, 0.14 ml of ethylene glycol diacrylate and 5 mg of azobisisobutyronitrile in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0041] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0042] Example 4

[0043] 2 g of hexadecyl acrylate, 0.14 ml of 1,6-hexanediol diacrylate and 5 mg of azobisisobutyronitrile were dissolved in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0044] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0045] Example 5

[0046] Dissolve 2 g of hexadecyl acrylate, 0.14 ml of 1,4-butanediol diacrylate, and 5 mg of azobisisobutyronitrile in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0047] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0048] Example 6

[0049] Dissolve 2 g of hexadecyl acrylate, 0.14 ml of ethylene glycol diacrylate and 5 mg of azobisisobutyronitrile in 3 ml of tetrahydrofuran to obtain a uniform solution;

[0050] The solution was transferred to a glass mold with a diameter of 5 cm and a height of 0.03 cm. The mold was placed in a reaction container and subjected to a temperature-controlled heat treatment at 90° C. for 4 h. The sample was then dried at room temperature to obtain a transparent phase change film.

[0051] The infrared analysis results of Examples 2 to 6 are similar to those of Example 1. Three different diacrylic acid monomers are used as cross-linking agents. The main purpose is to prepare six phase change film materials with different chain lengths. Since infrared absorption spectra are mainly used for group structure analysis, qualitative and quantitative analysis of materials, infrared spectra do not show obvious differences for materials with different chain lengths. Therefore, the infrared spectra of Examples 2 to 6 are not described in detail here.

[0052] Performance Testing

[0053] 1. The phase change film prepared in Example 1 is as follows Figure 1 As shown in the figure, it can be seen that at room temperature of 25°C, the prepared phase change film exhibits high transparency and high transmittance, and the difference is very small compared with the blank example not covered with any film (the actual phase change film prepared in Examples 2 to 6 has a transparency similar to that presented in Example 1, which will not be repeated).

[0054] 2. The transmittance of the phase change films obtained in Examples 1 to 6 was tested in the visible light region at room temperature. The test results are as follows:

[0055] sample Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Light transmittance 95.4% 95.7% 96.2% 96.8% 97.7% 98.2%

[0056] 3. Photoelectric conversion efficiency experiment:

[0057] The phase change film prepared in Example 1 is placed close to a piece of 2 The front side of the polycrystalline silicon solar cell panel is encapsulated, and then an external aluminum wire is connected to conduct electricity to assemble into a solar cell, and a thermal management system is established to study the effect of the phase change film prepared in Example 1 on the photoelectric conversion efficiency;

[0058] The parameters were measured by a solar simulator (SS-F5-3A, Enlitech, China) with an AM 1.5 solar spectrum filter and a solar radiation power density of 100 mW / cm 2 ; Reverse voltage scan rate (from 1.2V to 0.2V) is 0.02Vs -1 , the delay time is 0.1s; the photoelectric conversion efficiency (PCE) is calculated from the JV curve; the experimental results are shown in Figure 3 , see the specific packaging diagram Figure 4 ;

[0059] Through the blank control samples, it can be seen that the photothermal conversion efficiency of the polycrystalline silicon solar cell without a thermal management system increases from room temperature to 77°C after 580s of solar radiation, and the corresponding photoelectric efficiency drops sharply from 16.6% to 11.6%, a decrease of 5 percentage points; the temperature of the sample using the phase change film of the embodiment vegetation in the photovoltaic system rises slowly, and a constant temperature platform appears at around 35°C at 200s. This platform is the heat storage platform of the phase change film. At this time, the phase change film absorbs heat and stores it when it changes from a crystalline state to an amorphous state, thereby keeping itself and the solar panel at a constant temperature. At this time, the photoelectric efficiency only drops from 16.6% to 14.7%, a decrease of only 1.9 percentage points. Compared with the blank sample, it drops to 11% after 1140s, and the corresponding polycrystalline silicon photovoltaic panel rises to 79°C, with a time delay of 940s; the above results show that the phase change film prepared in Example 1 has a good thermal regulation effect and can improve the photoelectric conversion efficiency of the photovoltaic system within a certain period of time.

[0060] The experimental results of Examples 2 to 6 are similar to those of Example 1 and will not be described in detail here.

[0061] 4. Determine the enthalpy values ​​of the raw materials and finished products of the transparent phase change films obtained in Examples 1 to 6; the test method is to use a thermal analyzer (Q-20, TA Instruments, USA) in the temperature range of -10-80°C at 10°C min -1 The heating and cooling rates were tested, and the experimental raw materials and experimental results of each embodiment are shown in Table 1; as the alkyl chain of the cross-linked material increases, each embodiment shows an increase in enthalpy value, and the melting point and critical temperature move toward high temperature. This is because the cross-linking density of the polymer network increases, and the high cross-linking density limits the freedom of movement of the polymer chain segments, thereby reducing the arrangement and rearrangement ability of the polymer chain segments, resulting in an increase in the melting point and critical temperature, indicating that the alkyl carbon in the cross-linked segment is crystalline. Under the condition of suitable chain length, the material can achieve excellent enthalpy value and show better light transmittance and heat storage capacity.

[0062] Table 1

[0063]

[0064] ΔH m : Melting enthalpy Melting start temperature Fastest melting temperature

[0065] ΔH c : Crystallization enthalpy Crystallization start temperature Fastest crystallization temperature

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a phase change film with high light transmittance at room temperature, characterized in that: The steps include: S1. Dissolving a polymerized phase change monomer, a polymerized cross-linking agent and an initiator in a solvent to obtain a solution; wherein the polymerized phase change monomer is one or a combination of octadecyl acrylate and hexadecyl acrylate; and the polymerized cross-linking agent is one or a combination of 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate and ethylene glycol diacrylate; S2. Injecting the prepared solution into a mold, heat treating it, and drying it at room temperature to obtain the transparent phase change film.

2. The method for preparing a phase change film with high light transmittance at room temperature according to claim 1, characterized in that: The initiator is a combination of one or more of azobisisobutyronitrile, azodimethylcapronitrile and dibenzoyl peroxide.

3. The method for preparing a phase change film with high light transmittance at room temperature according to claim 1, characterized in that: The solvent is a combination of one or more of tetrahydrofuran, dichloromethane, ether and chloroform.

4. The method for preparing a phase change film with high light transmittance at room temperature according to claim 1, characterized in that: The mass ratio of the polymerized phase change monomer to the polymerized cross-linking agent is 10:1-3.

5. The method for preparing a phase change film with high light transmittance at room temperature according to claim 4, characterized in that: The volume ratio of the total mass of the polymerized phase change monomer and the polymerized cross-linking agent to the solvent is 0.2-0.5 g / ml.

6. The method for preparing a phase change film with high light transmittance at room temperature according to claim 4, characterized in that: The molar amount of the initiator accounts for 0.1% to 10% of the total molar amount of the polymerized phase change monomer and the polymerized cross-linking agent.

7. The method for preparing a phase change film with high light transmittance at room temperature according to any one of claims 1 to 6, characterized in that: The heat treatment is specifically: continuing the reaction at 60-150° C. for 2-24 hours.

8. A room temperature high light transmittance phase change film, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. The use of the room temperature high light transmittance phase change film according to claim 8, characterized in that: Application in the field of thermal management in normal temperature transparent scenes.